Study of insulin levels in hypothyroidism patients - Rajeswari, Guddanti; Gopal, Pasagadugula Satya; Srinivas, Pasagadugula Satya; Suresh, Eadala (International Journal of Research in Medical Sciences, 2017)
Background: Overt hypothyroidism is an established risk factor for insulin resistance. In this study we find out whether this association exists between insulin resistance and subclinical hypothyroidism. Methods: Serum Insulin, Fasting blood sugar, Cholesterol were estimated in 60 clinically diagnosed patients of hypothyroidism these patients were divided in to two groups as group I, 30 overt hypothyroidism and group II, 30 subclinical hypothyroidism. Results were compared with a group of 30 normal subjects.To measure the level of insulin resistance using HOMA IR software. Results: In our study total cholesterol were significantly high in both overt hypothyroidism and sub clinical hypothyroidism as compared to euthyroid control group and serum TSH and serum insulin levels were positively correlated with total cholesterol levels in hypothyroidism patients. We also found that TSH levels were positively correlated with insulin and HOMA IR in patients with subclinical hypothyroidism. Conclusions: Hence it will be good practice to screen people for presence of subclinical hypothyroidism and insulin resistance for early detection and prolong the appearance of various fatal complications associated with insulin resistance in hypothyroidism.